What makes people adapt together? An empirically grounded conceptual model on the enablers and barriers of collective climate change adaptation - Wannewitz, Mia; Petzold, Jan; Garschagen, Matthias (Frontiers in Climate, 2023)
Coping with and adapting to climate change impacts are collective action problems that require broad joint efforts to reduce current and future risks. This is most obvious for highly vulnerable and exposed individuals, whose capacities to adapt to recurrent environmental threats are mostly bound in their ability to work together – not only in the immediate disaster situation but also in the long-term to secure their livelihoods. While there are explanatory models for collective action in the context of climate change, there is still a need to validate them further for vulnerable residents in high-risk contexts that prioritize cultural values of collective self-understanding, mutual support, and reciprocity. Additionally, the identified factors that facilitate collective climate action are currently quite abstract and may not be very useful for practical application and policy development. Addressing these gaps, we build on existing collective action models and a qualitative analysis of empirical data from kampung cooperatives in Jakarta to develop a conceptual framework explaining what triggers individuals to start acting collectively and which factors motivate them to keep being engaged in long-term collective adaptation action. It highlights the need to differentiate between what we will call initial triggers and long-term motivators to better understand and advance collective adaptation efforts in high-risk contexts. This novel differentiation of motivation factors enhances our conceptual understanding of collective adaptation. Furthermore, the findings may inform practice and policy-making toward enhancing and maintaining collective adaptation initiatives.